2020
DOI: 10.1073/pnas.2007773117
|View full text |Cite|
|
Sign up to set email alerts
|

Neural progenitor cell pyroptosis contributes to Zika virus-induced brain atrophy and represents a therapeutic target

Abstract: Mounting evidence has associated Zika virus (ZIKV) infection with congenital malformations, including microcephaly, which raises global alarm. Nonetheless, mechanisms by which ZIKV disrupts neurogenesis and causes microcephaly are far from being understood. In this study, we discovered direct effects of ZIKV on neural progenitor cell development by inducing caspase-1– and gasdermin D (GSDMD)-mediated pyroptotic cell death, linking ZIKV infection with the development of microcephaly. Importantly, caspase-1 depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 54 publications
1
47
3
3
Order By: Relevance
“…In addition to the maturation of IL-1β, NLRP3 activation confers the release of IL-1β via pyroptosis, a newly discovered caspase-1-dependent programmed cell death process [ 13 ], occurs in multiple tissues, including brain [ 14 , 15 ]. In mice, pyroptosis acts downstream of the NLRP3 inflammasome, which transforms procaspase-1 into cleaved caspase-1 and then cleaves gasdermin (GSDM) family proteins, mostly GSDMD, to generate GSDMD N-termini and then form pores on the plasma membrane for IL-1β release [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the maturation of IL-1β, NLRP3 activation confers the release of IL-1β via pyroptosis, a newly discovered caspase-1-dependent programmed cell death process [ 13 ], occurs in multiple tissues, including brain [ 14 , 15 ]. In mice, pyroptosis acts downstream of the NLRP3 inflammasome, which transforms procaspase-1 into cleaved caspase-1 and then cleaves gasdermin (GSDM) family proteins, mostly GSDMD, to generate GSDMD N-termini and then form pores on the plasma membrane for IL-1β release [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation represents an additional mechanism of host responses to pathogens, and ZIKV infection in newborns has been shown to induce the production of inflammatory cytokines [ 49 , 50 ]. NOD-like receptors (NLRs) are responsible for the assembly of inflammasomes, which are signaling complexes involved in caspase-1-dependent innate immunity involving cytokines, such as IL-1β, and in the induction of cell death by pyroptosis [ 16 , 51 , 52 ]. ZIKV-induced microcephaly has highlighted monocytes as potential carriers that can cross the placenta to transmit ZIKV to the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV reduces NPC proliferation, induces their premature differentiation, and activates apoptosis of NPCs and immature neurons [ 14 ]. In terms of cell death pathways activated by the inflammatory response, pyroptosis, necrosis, and necroptosis have also been studied in the context of ZIKV infection and microcephaly [ 15 , 16 , 17 ]. Nevertheless, a question remains as to the detailed mechanisms through which ZIKV causes cytotoxic effects during neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Low concentrations of betulinic acid showed to be neuroprotective, increasing the number of SOX2 + NPC in ZIKV-infected brain organoids ( Cavalcante et al, 2020 ). Although apoptosis is able to reduce the neuronal cell populations affecting the brain structure, other types of cell death are involved, such as pyroptosis ( He et al, 2020 ). The presence of inflammatory cytokines and necrotic tissue suggests the occurrence of pyroptosis characterized by the activation of inflammasomes, caspase-1 and gasdermin D, being strongly inflammatory and differing from apoptosis, which is a silent process.…”
Section: The Aftermath Of Zikv Infection: Prenatal Neuronal Impairmenmentioning
confidence: 99%
“…This occurs due to the leakage of intracellular content and cleavage of IL-1β and IL-18, two pro-inflammatory cytokines ( Shi et al, 2015 ; de Sousa J. R. et al, 2018 ). The analysis of brain tissue collected from newborn fatal cases of ZIKV-linked microcephaly revealed increased levels of inflammasome activation of IL-1β in parenchyma suggesting a pivotal role of pyroptosis ( de Sousa J. R. et al, 2018 ) and, so far, pyroptosis is confirmed in NPC ( He et al, 2020 ).…”
Section: The Aftermath Of Zikv Infection: Prenatal Neuronal Impairmenmentioning
confidence: 99%